MENGHADAPI PENDERITAAN: MAKNA KEBEBASAN DALAM FILSAFAT EKSISTENSIALISME JEAN-PAUL SARTRE - Kako, Bryan; Paskalis Vantura Noto; Sebastianus Parman (Sanjiwani: Jurnal Filsafat, 2026)
This article explores the meaning of freedom within the context of existentialist philosophy, particularly through the perspective of Jean-Paul Sartre, with a focus on how this concept of freedom can help individuals cope with suffering and find meaning in life. In the modern era, where humans enjoy extensive freedom in various aspects of life, freedom is often misunderstood and exercised without moral consideration, leading to conflict and social instability. This article demonstrates that true freedom in existentialism is not merely the right to choose, but also full responsibility for one’s choices and their consequences. Suffering, which is an integral part of human existence, is inevitable, and by accepting it, individuals can discover the meaning and purpose of life. Existentialism invites us to understand freedom as responsibility and awareness, and to face suffering with full responsibility and meaning. Thus, individuals can create a more meaningful identity and purpose in life, as well as contribute positively to society.